Surgical vs. Non-Surgical Treatment Modalities for Temporomandibular Joint Ankylosis: A Comparative Study - Kiran Tyagi; Sachin Dev; Vishal Bharadwaj; Bishwadeep Borah; Avinash Chandra Choudhary; Pawan Mittal (Oral Sphere Journal of Dental and Health Sciences, 2026)
Background: Temporomandibular joint (TMJ) ankylosis is a form of debilitating condition that causes the fusion of the TMJ resulting in limited movement of the jaw. The use of treatment methods such as surgery and non-surgery has proven to contain different results in the cases of a given ankylosis depending on the severity of the ankylosis. The proposed research is aimed at comparing the efficacy of both surgical and non-surgical modalities of treatment of TMJ ankylosis in terms of jaw mobility, pain relief, facial symmetry and patient satisfaction. Methods: The comparative study has been carried out on 120 patients with TMJ ankylosis, who were divided into two groups; 60 patients treated using surgery and 60 patients treated using non-surgery. The data related to the jaw mobility, level of pain, facial symmetry and patient satisfaction were measured at the baseline and after 6 months, 1 and 2 years of treatment. To compare the two treatment groups using statistical analysis, paired t -tests and independent t -tests were used to determine the differences. Results: The surgical group thus showed significantly better improvements in jaw movement (35mm vs 18mm), range (42% vs 22%), pain relief (reduction in VAS score 7.521 vs 7.334) and facial symmetry (85% vs 60%). The surgical cohort also had higher levels of patient satisfaction (8.7 versus 6.5). However, there were complications like ankylosis recurring and weakness of the facial nerves in the surgical group, but the non-surgical group needed further interventions in some cases. Conclusion: TMJ ankylosis surgical interventions produce better results in regard to customer satisfaction, pain alleviation, symmetrical facial form, and jaw range compared to non-surgical interventions. Non-surgical treatments are effective in the mild cases but could not result in adequate improvements in patients with severe ankylosis. The individualized treatment based on a specific severity of the condition is suggested to guarantee the best patient outcomes.